3D-printed silicate porous bioceramics using a non-sacrificial preceramic polymer binder. (22nd May 2015) - Zocca, A; Elsayed, H; Bernardo, E; Gomes, C M; Lopez-Heredia, M A; Knabe, C; Colombo, P; Günster, J
Abstract: Silicate bioceramics possess an excellent bioactivity; however, shaping them into complex geometries is still challenging. Therefore, this paper aims to present a new strategy for the shaping of a bioglass-ceramic with controlled geometry and properties starting from a glass powder combined with a preceramic polymer, i.e. a silicon resin, and reactive fillers. The powder-based three-dimensional (3D)-printing of wollastonite (CaSiO3 )-based silicate bioceramic parts was demonstrated in this work. The resin plays a dual role, as it not only acts as a non-sacrificial binder for the filler powders in the printing process but it also reacts with the fillers to generate the desired bioceramic phases. The mechanical and physical properties, i.e. ball-on-three-balls test, density, porosity and morphology, were evaluated in 3D-printed discs. These samples possessed a total porosity around 64 vol% and a biaxial flexural strength around 6 MPa. The raw materials used in this work also enabled the 3D-printing of scaffolds possessing a designed multi-scale porosity, suitable bioceramic phase assemblage and a compressive strength of 1 MPa (for cylindrical scaffolds with total porosity ∼80 vol%). Solubility in TRIS/HCl and in vitro assays, i.e. viability, cytotoxicity and apoptosis assays, were also performed. In vitro tests indicated good cell viability and no cytotoxicity effect on the cells.